2004
DOI: 10.1116/1.1761186
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of hafnium oxide and hafnium silicate thin films using liquid precursors and ozone

Abstract: Atomic layer deposition (ALD) processes for HfO2 and HfxSi1−xO2 high-k dielectric thin films using liquid precursors and ozone were evaluated. Tetrakis(ethylmethylamino)hafnium (TEMAHf) precursor provides HfO2 films with superior quality as compared to Hf(t-butoxide)4 precursor in terms of deposition rate, purity, and electrical properties of the films. ALD processes for hafnium silicate films have been developed by co-injection of TEMAHf and tetrakis(ethylmethylamino) silicon precursors. Alternating pulses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 9 publications
4
78
2
Order By: Relevance
“…Hafnium compounds belonging to the group of alkylamides, e.g. Hf(NEtMe) 4 have been widely applied with water or ozone as the oxygen source to produce HfO 2 films [8][9][10][11]. Their volatility, reactivity and resulting high growth rate of HfO 2 can be considered as clear advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Hafnium compounds belonging to the group of alkylamides, e.g. Hf(NEtMe) 4 have been widely applied with water or ozone as the oxygen source to produce HfO 2 films [8][9][10][11]. Their volatility, reactivity and resulting high growth rate of HfO 2 can be considered as clear advantages.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the electrical properties of HfO 2 can be improved by adding different elements such as N, Si, Al, Ti, Zr and Ta. [5][6][7] ZrO 2 is isomorphous to HfO 2 with a similar structure, 8 it is also the only thermodynamically stable solid form of zirconium with a simple fluorite structure. The tetragonal ZrO 2 and HfO 2 both have the highest dielectric constant (k∼40-50) whereas the monoclinic ZrO 2 has the lower dielectric constant (k∼20).…”
Section: Introductionmentioning
confidence: 99%
“…Wafer EOTs were calculated using Hauser's CVC model [12]. The co-injection ALD employed for HfSiOx ALD [7] was further extended to grow HfSiN films from TEMAHf/Si vapor mixture pulses and alternating pulses of NH 3 . For ALD TiN films, a volatile liquid inorganic precursor (TiCl 4 ) was used.…”
Section: Methodsmentioning
confidence: 99%
“…MOCVD of ZrSiO x was explored using liquid metal amide precursors [4,5], and HfSiOx deposition has also been reported using analogous precursors [6]. Recent advances in equipment design have provided the capability for ALD to deposit HfSiOx films of varying compositions from volatile metal-organic precursors in both single-wafer ALD [7] and multi-wafer batch ALD platforms [8]. This paper explores devices utilizing both HfO 2 and Hf x Si 1-x O gate dielectrics deposited by ALD from metal alkylamide precursors and ozone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation